Cloning coat protein gene of CBSD (cassava brown streak disease) at cassava (Manihotesculentum) - Didik Pudji Restanto; Slameto .; Budi Kriswanto; Hardian Susilo Addy; Tri Handoyo (UNEJ e-Proceeding, 2014)
Cassava Brown Streak Disease (CBSD) is a major disease in cassava plants which have the serious problems in cassava plantations in the world, especially in Africa, Tanzania and India (Wassawaet., al, 2010). In Indonesia, the virus is still not optimal yet in the handling. The disease is present in plants that can destructive cassava leaves, stems and tubers.  It was greatly reduces the quality and production in the world such as India.  The decrease of cassava yield can reach 100% due to disease of CBSD (Lopez, 2003). The primer was designed from the coat protein gene of CBSD with a distance of 380 bp (Abarshiet.,al, 2012). The primers designed the forward primer (GGARCCRATGTAYAAATTTGC) and Reverse (GCWGCTTTTA  TYACAAAMGC). The RNA isolation have been used Plant Virus RNA Kit (Geneaid).  The CBSD RNA concentration around 55,2ng/ul.  The RT PCR program were one cycle of RT PCR reaction (45oC for 30 min), denaturation (45oC for 5 min) and 30 cycles for denaturation (94oC for 1 min), annealing (52oC for 30 sec), extention  (72oC for 1 min).  The results showed a single band of about 380 bp which is the  distance between the two primers were tested.  The multiplication shoot around 5 shoots per meristem explants with a combination of 0.5 ppm and 0.1 ppm BAP GA3 Keyword : Cassava Brown Streak Disease (CBSD), CASSAVA (Manihotesculentum), RT PCR